2001
DOI: 10.1111/j.1365-2621.2001.tb11332.x
|View full text |Cite
|
Sign up to set email alerts
|

Phytosterols and Fatty Acids in Fig (Ficus carica, var. Mission) Fruit and Tree Components

Abstract: The phytosterol compositions in unsaponifiables of fig (Ficus carica, var. Mission) fruit and 3 structural components of the branches; and the fatty acid composition of fig fruits were studied using gas chromatography (GC) and gas chromatography/mass spectrometry (GC/MS). The phytosterols were determined from the trimethylsilyl ether (TMS) derivatives of the unsaponifiable samples. Fourteen compounds were separated from fig fruit; 13, 10, and 6 in bark, stem, and pith, respectively. Sitosterol was the most pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
76
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(88 citation statements)
references
References 22 publications
11
76
1
Order By: Relevance
“…The polyphenol content in black raisin (271.67 mg GAE/100 g) was reported to be much lower compared to golden raisin. Golden raisins have higher total polyphenol content compared to other types of raisins based on data from USDA and PhenolExplorer (Williamson & Carughi, 2010 (Jeong & Lachance, 2001;Veberic et al, 2008;Slatnar et al, 2011). Dried figs are rich in dietary fiber, vitamin K and minerals such as magnesium, potassium and calcium (Vinson, 1999 Ajwa, Safawi and Mariami dates showed the highest total sugar content ranging from 43.75 to 48.61%.…”
Section: Discussionmentioning
confidence: 99%
“…The polyphenol content in black raisin (271.67 mg GAE/100 g) was reported to be much lower compared to golden raisin. Golden raisins have higher total polyphenol content compared to other types of raisins based on data from USDA and PhenolExplorer (Williamson & Carughi, 2010 (Jeong & Lachance, 2001;Veberic et al, 2008;Slatnar et al, 2011). Dried figs are rich in dietary fiber, vitamin K and minerals such as magnesium, potassium and calcium (Vinson, 1999 Ajwa, Safawi and Mariami dates showed the highest total sugar content ranging from 43.75 to 48.61%.…”
Section: Discussionmentioning
confidence: 99%
“…In traditional medicine the roots are used in the treatment of leukoderma and ringworm, and its fruits have antipyretic, purgative and aphrodisiac properties, and have been shown to be useful in inflammations and paralysis (Nadkarni & Nadkarni, 1995;Kirthikar & Bzasu, 1996). Earlier chemical examination of this plant has shown the presence of psoralen, bergapten, umbelliferone (Seong-Kuk et al, 1995;Louis et al, 2000), β-sitosterol, campesterol, stigmasterol fucosterol, fatty acids (Jeong & Lachance, 2001), 6-(2-methoxy-Ζ-vinyl)-7-methyl-pyranocoumarin and 9,19-cycloarlane triterpenoid as an anticancer Weiping et al, 1997) and antiproliferative agent; 6-Oacyl-β-D-glucosyl-β-sitosterol (Shai et al, 2001), calotropenyl acetate, and lupeol acetate (Saeed & Sabir, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…The leaves have been reported to have furanocoumarins including psoralen, bergapten, xanthotoxin [20] and triterpenes such as calotropenyl acetate and lupeol acetate [21]. The other valuable ingredients are phenolics, anthocyanins, fructose, glucose, and sucrose were identified from the figs [22] and the previous finding reported that fruit has phytosterols [23].…”
Section: Ingredients Of F Caricamentioning
confidence: 95%